Comprehensive Assessment of Anterior and Posterior Lingual Mandibular Depressions Using Cone Beam Computed Tomography: Morphology, Prevalence and Clinical Implications - Pishva, Seyyed Sajjad; Sarrafan, Negar; Ghaznavi, Aisan; Fathi, Paria (Galen Medical Journal, 2024)
<div class="min-h-8 text-message flex w-full flex-col items-end gap-2 whitespace-normal break-words [.text-message+&]:mt-5" dir="auto" data-message-author-role="assistant" data-message-id="7edf5381-d6bb-43bd-8d05-9d1a634c2923" data-message-model-slug="gpt-4o"> Background: Assessment of lingual mandibular depressions, has significant clinical relevance in various maxillofacial procedures. Cone Beam Computed Tomography (CBCT) has emerged as a valuable tool for the detailed evaluation of these anatomical features. The aim of this study was to comprehensively assess lingual mandibular depressions utilizing CBCT imaging. Materials and Methods: In this descriptive-cross-sectional study, 384 images from patients were examined. The images were reviewed using the Plunmeca Promax 3D device. the concavity depth, ridge thickness from the alveolar crest area, angle of concavity two millimeters above the inferior alveolar nerve, height of concavity from the start of the concavity to its end, and also the linear height along the occlusal plane with the opposing teeth in the lower jaw ridge were measured in the lingual area of the canine-premolar. Results: The frequency of concavity was 2.9% in the canine-premolar region, in the first molar region 34.7%, and in the second molar region 98.2%. The concavity depth in the canine-premolar region was measured at 4.41 millimeters, in the first molar region at 3.80 millimeters, and the second molar region at 4.43 millimeters. The concavity height was reported as 13.26 millimeters in the canine-premolar region, 12.35 millimeters in the first molar region, and 13.51 millimeters in the second molar region. The angle of concavity was measured at 60.48 degrees in the canine-premolar region. Ridge thickness in the canine-premolar region was 9.06 millimeters, in the first molar region 10.47 millimeters, and the second molar region 10.43 millimeters. No interference was found in the canine-premolar region, while interference was observed in 7.25% of cases in the first molar region and 23.6% in the second molar region. Conclusion: Imaging with CBCT should be performed before implant placement also the concavity depth in the area should be considered to avoid potential interference during implant placement.